CARNAP’S ALTERNATIVE TO LOGICAL PLURALISM, MONISM AND NIHILISM (Revista Kriterion, 2026)
Current literature offers a pluralist, a monist and a nihilist reading of Rudolf Carnap’s works. Despite their differences, these readings assume that, while determining which objects have the property of being a logicand that of being logically correct, Carnap’s works aim at answering a question: What is the number of correct logics? This exegetical essay challenges this assumption; it proposes a not yet explored reading according to which Carnap’s works point, even if only in a tentative fashion, to logical experimentalism. The latter sets itself up for three tasks. The first is to deflate the dispute about the number of correct logics in the sense of showing its lack of pertinence. The second task is to react in a bottom-top way to the fact that those who use “logic” – say, to describe a use of language that they adopt – have and probably will continue to decide on their own what properties are those of the object, which they describe with this term. The third task is to settle a condition for dialogue with these users, while seeking to have a constructive interaction with them within a particular context of application of the term, “logic”.